Sub-Types and Treatment Outcomes of adolescent and Adult Non-Hodgkin Lymphomas in a Resource Poor Setting - Dei-Adomakoh, YA; Asare, EV; Amedonu, ESA; Abrahams, ED; Segbefia, CI; Acquaye, JK (Journal of Hematology and Oncology Research, 2017)
Background: The diagnosis and treatment outcomes of Non- Hodgkin Lymphoma’s (NHL) in resource poor countries in the absence of routine molecular studies and immunohistochemistry is challenging. Methods: A retrospective review of case folders of NHL patients aged13 years and above. Information obtained from the case folders included age, sex, histological subtype, subtypes using the Working Formulation and WHO classifications. Treatment given and follow up information were also evaluated. Results: A total of 279 cases of NHL were identified within the study period. The mean age of the patients was 48.8 ± 17.0 years. The male to female ratio was approximately 1.5:1. The majority of cases seen (53%) were diffuse large B- cell lymphoma. Chronic lymphocytic leukaemia/ small lymphocytic lymphoma (22.2%) was the next most common subtype. Other sub types seen, in order of frequency, included diffuse mixed cell lymphoma (6.4%), gastric lymphomas (3.9%), mediastinal B- cell lymphoma (2.9%), Burkitt’s lymphoma (1.8%), splenic marginal zone B-cell lymphoma (1.1%), lymphoblastic lymphoma (1.1%), mucosa- associated lymphoid tissue (MALT) type B- cell lymphoma (0.7%) and follicular lymphoma (0.7%). Conclusion: This study provides an overview of the distribution of NHL subtypes and their outcomes in a resource constrained setting. Immunohistochemistry, cytogenetics and specific molecular studies which are important in characterization of NHLs, should be made affordable and accessible in low income countries.
Keywords: Histological subtypes; Treatment; Non-Hodgkin lymphoma; working formulation; Ghana